Multifunctionality of Organic Farming: Case Study from Southern Poland - Śpiewak Ruta (European Countryside, 2016)
The main goal of this article is to answer the question whether organic farming, which is developing in some parts of Poland, can be considered as a form of multifunctional farming and contribute so to non-commodity functions and the process of change in a particular territory of given areas. The analyses are based on data obtained from 2013 of several points in the south of Poland representing a cluster of organic market oriented farmers. The results show that namely market organic farming may serve as multifunctional one, but only under certain conditions and for a specific type of farming. Through specific functions, organic farming facilitates the changes, primarily on a local scale. The existence of a strong integrated organic farming sector might influences development and change, resulting in not only the improvement of economic welfare of organic farmers, but also of whole local communities, strengthening the bonds amongst them, mobilising the social resources.